Hubungan Belajar Online di Masa Pandemi Covid 19 dengan Tingkat Stress Mahasiswa S1 Keperawatan STIKes Baiturrahim Jambi - Adrian, Fadhil Ammar; Putri, Vevi Suryenti; Suri, Marta (Universitas Baiturrahim, 2021)
As a result of the global Covid-19 pandemic, all campuses are being led to conduct online or online lectures in order to break the chain of Covid-19 spread.Online learning is a type of teaching-learning activity with technology that is carried out remotely. All elements ranging from lecturers, staff, and students must adapt to this condition. This sudden change can certainly cause stress to studentsmethodThis researchuses a quantitative research method with a cross-sectional. The population in this study were undergraduate nursing students at STIKes Baiturrahim Jambi. The researchwas conducted online by filling out questionnaires via google form. The data obtained were analyzed univariately and bivariately using the chi square test, the study was conducted on 23-24 June 2020. The results of 57 respondents as many as 25 (43.9%) learning online is not good and as many as 32 (56.1%) learning online is good. Online learning of the majority of undergraduate nursing students is good. Of the 57 respondents, 32 (56.1%) had light stress levels, 16 (28.1%) moderate stress levels and 9 (15.8%) severe stress levels. The results of statistical tests obtained p-value = 0,000..The conclusion is that there is a relationship between online learning and the stress level of S1 Nursing STIKES Baiturrahim Jambi students